Role of HEG1 and Claudin-4 Immunohistochemistry in the Differential Diagnosis of Lung Adenocarcinoma from Malignant Mesothelioma in Pleural Effusion Cytology - Aziza E. ABDELRAHMAN; Fatma A. ELBADRY; Taiseer R. IBRAHIM; Mohamed Ali ALABIAD; Mohamed AWAD (Türk Patoloji Dergisi, 2025)
Objective: Cytological examination of pleural effusion is minimally invasive and low risk but faces challenges due to the lack of architectural features, low cell counts, and overlapping characteristics among reactive mesothelial cells (RMCs), carcinoma cells, and malignant epithelioid mesothelioma (MPM) cells. The aim of this was study to detect the diagnostic accuracy of the expression of HEG1 and Claudin-4 in distinguishing malignant mesothelioma from lung adenocarcinoma in pleural effusion. Material and Methods: The present study was carried out on 84 cases of pleural effusion. Sixty-four representative cell blocks of the studied malignant cases and twenty control cases were stained with HEG1 and Claudin-4 immunostaining, and the results were recorded. Results: Positive membranous HEG1 immunoexpression was found in 95% of RMCs in benign effusions. Also, positive membranous HEG1 immunoexpression was found in 96% of cases of MPM, and only 2.6% of lung adenocarcinoma cases. There was a statistically significant difference between benign effusion with RMCs and lung adenocarcinoma immunoreactivity. There was a highly statistically significant difference between HEG1 immunoexpression in MPM and lung adenocarcinoma. On the other hand, all cases of benign effusions and all MPM cases had negative Claudin-4 immunoexpression while positive membranous Claudin-4 immunoexpression was found in 94.9% of lung adenocarcinoma cases. There was a statistically significant difference in immunoexpression of Claudin-4 between benign effusion and lung adenocarcinoma. There was a statistically significant difference in the immunoexpression of Claudin-4 between MPM and lung adenocarcinoma. Conclusion: HEG1 and Claudin-4 IHC staining is extremely valuable in the differential diagnosis between reactive or malignant mesothelial cells and adenocarcinoma in pleural effusion.